ANALISIS FAKTOR FAKTOR YANG MEMPENGARUHI KEJADIAN GIZI KURANG PADA ANAK BALITA DI WILAYAH KERJA PUSKESMAS SAITNIHUTA KECAMATAN DOLOKSANGGUL KABUPATEN HUMBANG HASUNDUTAN - Natalia Sihombing; Albiner Siagian; Fitri Ardiani (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2017)
Malnutrition may induce unavoidable bad consequences, where the worst manifestation can lead to death. The purpose of this study was to analyze the influence of risk factors on the incidence of malnutrition among under five children in Saitnihuta Health Center work area.   This research used observasional method with cross sectional design. The sampling technique used the total population with the number of samples as many as 64 under nutrition childrens than 12-59 months of age. Data collection techniques using questionnaires and food recall form 24 hours. Data analysis technique using chi square analysis.   The results, 89.1% under nutritious nutrition and 10.9% under severe nutrition. Mother knowledge variable with ρ-value (0.004)<0,05, family income with ρ-value (0,014)<0,05, completeness of immunization ρ-value (1,000)>0,05, exclusive breastfeeding with result ρ -value (0.030) <0.05, food intake with ρ-value (0.012)<0.05, infectious diseases with ρ-value (1,000)> 0.05.   The conclusions of this research are the variables that affect the incidence of malnutrition among under five children in the working area of Saitnihuta Public Health Center were the level of family income, and food intake. Family income are the most influential variable on the incidence of malnutrition in children under five in Saitnihuta Health Center work area. Based on research results the result of the research, it is hoped to Saitnihuta Health Center to doing health education conseling in posyandu’s to pregnant mothers and to mothers who have under five children about nutrition intake in under five children. And to the local government are expected to further empower the community or develop infrastructure in improving family income and to mothers who have under five children are expected to be more actively participate in posyandu activities every month.     Keywords: Under Nutrition, Food Intake, Exclusive Breastfeeding, Under five Children